A review of potential applications of Tensor Decompositions to Electromagnetics and energy works - Mageed, Ismail A; Yilmaz, Musa; Zhang, Quichun; Celikel, Resat; Sidhu, Manjit Singh (Institute of Electrical and Electronics Engineers Inc., 2022)
The approaches for tensor decomposition (TD) are reviewed in this study. For uncertainty quantification and electromagnetic (EM) solvers, we cover their applications to surrogate modeling (SM). The current study Discussion is undertaken regarding the significant impact of these decompositions on lowering memory. Additionally, the influential role of TDs in energy research is thoroughly reviewed. The latter review consolidates more foundational motivations and insights into further employment of TDs to advance research works. Conclusions and future directions are given. © 2022 IEEE.
2022 IEEE Global Energy Conference, GEC 2022 -- 26 October 2022 through 29 October 2022 -- Batman -- 185674
Keywords: canonical polyadic (CP); EM analysis; EM solvers; energy works; SM; smart grid; TD